2005
DOI: 10.3748/wjg.v11.i11.1639
|View full text |Cite
|
Sign up to set email alerts
|

Serum IL-6, TNFα and CRP levels in Greek colorectal cancer patients: Prognostic implications

Abstract: AIM:The significance of preoperative serum IL-6, TNF and CRP levels in the progression of colorectal cancer (CRC) has not been fully elucidated. Our intention was to investigate their role and identify their prognostic significance. METHODS:The IL-6, TNF and CRP levels were measured in 74 CRC patients and the relationships between their elevations and both the clinicopathological factors and prognosis of patients w ere inves tigated. Serum concentrations of human IL-6 and TNF were determined by enzyme-linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
99
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 23 publications
(35 reference statements)
15
99
0
6
Order By: Relevance
“…Also, a number of studies carried out in primary operable colo-rectal cancer have highlighted the independent prognostic value of an elevated C-reactive protein concentration (55)(56)(57)(58)(59)(60)(61)(62) , with only two studies failing to observe such a relationship (63,64) . Recently, the prognostic value of the GPS has been examined in patients with either primary operable colorectal cancer (n 149) or synchronous unresectable liver metastases (n 84) (65) .…”
Section: Application Of a Systemic-inflammation-based Score In Patienmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a number of studies carried out in primary operable colo-rectal cancer have highlighted the independent prognostic value of an elevated C-reactive protein concentration (55)(56)(57)(58)(59)(60)(61)(62) , with only two studies failing to observe such a relationship (63,64) . Recently, the prognostic value of the GPS has been examined in patients with either primary operable colorectal cancer (n 149) or synchronous unresectable liver metastases (n 84) (65) .…”
Section: Application Of a Systemic-inflammation-based Score In Patienmentioning
confidence: 99%
“…McMillan et al (55) Colo-rectal 36 Post-op CRP stage independent Nozoe et al (56) Colo-rectal 120 Pre-op CRP stage independent Nielsen et al (57) Colo-rectal 456 Pre-op CRP stage independent Wigmore et al (63) Colo-rectal 202 Pre-and post-op CRP not stage independent McMillan et al (58) Colo-rectal 174 Pre-and post-op CRP stage independent Chung et al (64) Colo-rectal 172 Pre-op CRP not stage independent Nikiteas et al (59) Colo-rectal 74 Pre-op CRP stage independent Crozier et al (60) Colo-rectal 222 Pre-op CRP stage and treatment independent Wong et al …”
Section: Application Of a Systemic-inflammation-based Score In Patienmentioning
confidence: 99%
“…Moreover, a Greek study demonstrated that high levels of serum IL-6, TNF-α and CRP were correlated with larger tumor size. The relation to tumor size could be related to the fact, that larger tumors may trigger a more potent immunological response manifested by the circulation of proinflammatory cytokines such as TNF-α [56] . PPAR-γ PPAR-γ, a ligand-activated transcription factor, is a key regulator of adipogenic differentiation and glucose homeostasis.…”
Section: Inflammatory Cytokines and Colorectal Cancermentioning
confidence: 99%
“…Chez l'homme, il a été montré qu'elle pouvait bloquer la maturation des cellules dendritiques [33]. De plus, le niveau d'IL-6 présent dans le sérum de patients atteints de cancer colorectal a été associé avec la taille de la tumeur, la progression tumorale, ainsi qu'avec une survie plus courte [34]. L'IL-1 a comme sources principales les macrophages et les cellules dendritiques.…”
Section: La Prostaglandine E2 (Pge2)unclassified